Nanocrystalline CoOx glass for highly-efficient alkaline hydrogen evolution reaction. Issue 1 (8th December 2022) - Feng, Jinxian; Qiao, Lulu; Zhou, Pengfei; Bai, Haoyun; Liu, Chunfa; Leong, Chon Chio; Chen, Yu-Yun; Ip, Weng Fai; Ni, Jun; Pan, Hui
Abstract : We report that the nanocrystalline CoO x glass composed of mixed amorphous parts and crystalline domains shows high-performance for electrochemical hydrogen production because of the synergistic effects among the nanocrystals and amorphous matrix. Abstract : Hydrogen evolution reaction (HER) is a vital step for green-hydrogen production in commercial alkaline water electrolyzers. Although various electrocatalysts have been developed, the relationship between the structure and HER activity has not been clearly understood. Herein, we report nanocrystalline CoO x glass composed of mixed amorphous parts and crystalline domains on Ni foam (NF) (denoted as (10CeCrP)CoO x –NF–HER) for alkaline HER. We find that (10CeCrP)CoO x –NF–HER exhibits high catalytic activity (for example, −0.354 V at 200 mA cm −2 without iR correction) and good stability at high current density. Our experimental results reveal that the synergistic effects between the nanocrystalline domains and amorphous matrix improve the HER kinetics dramatically because: (1) the amorphous CoO x enhances the pseudocapacitive K + adsorption, leading to high surface water affinity, (2) the mixed crystalline and amorphous structure improves the stability of CoO x in the HER process, leading to long-term catalytic stability, and (3) the high water and hydrogen concentrations on its surface provide abundant feedstocks for HER and promote the hydrogen transportation and conversion. Our findings may provide an insightful understanding for the enhanced catalytic performance of poor-crystalline electrocatalysts in HER, and open a new avenue for the design of high-performance HER electrocatalysts.